2008
DOI: 10.1136/thx.2007.080903
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2 systemic production in patients with asthma with and without aspirin hypersensitivity

Abstract: Background: A special regulatory role for prostaglandin E 2 has been postulated in aspirin-induced asthma. A study was undertaken to investigate the effects of aspirin on the systemic production of prostaglandin E 2 and cysteinyl leucotrienes in patients with asthma. Methods: The urinary concentrations were determined of two main prostaglandin E 2 metabolites (13,14-dihydro15keto-PGE 2 using a commercial enzyme immunoassay and 9,15-dioxo-11a-hydroxy-2,3,4,5-tetranor-prostane-1,20-dioic acid by gas chromatograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
50
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 53 publications
(45 reference statements)
5
50
1
1
Order By: Relevance
“…This is in contrast to Schafer et al [34] who found reduced basal levels of PGE 2 in peripheral blood cells; however, they also observed that arachidonic acid stimulation resulted in increased PGE 2 levels, which were not different between aspirin-tolerant and AERD patients. We found that pretreatment with acetylsalicylic acid caused inhibition of PGE 2 by more than 80% in both groups, which is in contrast to findings of Mastalerz et al [32] who described that the concentration of PGE metabolites in urine was not inhibited by aspirin in aspirin-sensitive patients. It should be noted, however, that this measurement also involves the renal tubular generation of PGE 2 .…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…This is in contrast to Schafer et al [34] who found reduced basal levels of PGE 2 in peripheral blood cells; however, they also observed that arachidonic acid stimulation resulted in increased PGE 2 levels, which were not different between aspirin-tolerant and AERD patients. We found that pretreatment with acetylsalicylic acid caused inhibition of PGE 2 by more than 80% in both groups, which is in contrast to findings of Mastalerz et al [32] who described that the concentration of PGE metabolites in urine was not inhibited by aspirin in aspirin-sensitive patients. It should be noted, however, that this measurement also involves the renal tubular generation of PGE 2 .…”
Section: Discussioncontrasting
confidence: 56%
“…In contrast, no differences in PGE 2 and COX were detected at basal conditions in fibroblasts from nasal polyps and bronchial tissue, but when stimulated, reduced PGE 2 release and COX-2 induction were observed [30,31]. Also, the basal levels of urinary PGE 2 metabolites of AERD patients were not different from those of healthy controls [32], while elevated PGE 2 levels in bronchoalveolar lavage fluid were detected in AERD patients, which were inhibited by aspirin challenge [33]. In our study, we found no differences in PGE 2 release, neither under basal nor LPS-stimulated conditions in adherent monocytes isolated from peripheral blood of AERD patients and healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral blood leukocytes and bronchial fibroblasts of AH patients undersynthesize PGE 2 at baseline, which places them at a disadvantage as they lack sufficient amounts of this anti-inflammatory prostaglandin to antagonize the proinflammatory action of leukotrienes. Recent studies by Roca-Ferrer et al [43] and Mastalerz et al [44] support the hypothesis of COX-1-dependent PGE 2 control of inflammation in aspirin hypersensitivity.…”
Section: Discussionmentioning
confidence: 77%
“…Against the background of insufficient COX-2-derived PGE 2 production, COX-1-derived PGE 2 may become crucial to maintain an unstable eicosanoid balance in the airways [44]. The altered response of inflammatory cells to aspirin may also be involved in this process, but it cannot be excluded that changes in receptor expression prelude the symptoms of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Patterns of eicosanoid mediators in subjects with AIA have previously been reported in several biological matrices: blood plasma, 15 bronchoalveolar lavage fluid, 16 nasal lavage fluid, 17,18 sputum, 19,20 and urine 21,22 and, to a much lesser extent, EBC. 23,24 After the oral aspirin challenge test, the starkest differences in eicosanoid production were found in urine, 21,22 reflecting increased systemic biosynthesis of cysteinyl LTs, the main eicosanoid culprit for asthmatic attack. In aspirin-intolerant subjects, even those in stable clinical condition, increased LTE 4 urinary excretion is a hallmark of the disease.…”
Section: Discussionmentioning
confidence: 93%